Analisis Potensi Energi Biomassa dari Limbah Sekam Padi Menggunakan Model Stokastik (Monte-Carlo) untuk Mendukung Ketahanan Energi dalam Upaya RPJPN Indonesia - Altamis Ahnaf Esalka; Rasyid Putra Ariyani; Arifin Aji Nugroho; Widayoko, Agus (SMA Trensains Muhammadiyah Sragen, 2026)
Indonesia generates a large amount of rice-based agricultural residues, particularly rice husk, which contains lignocellulosic compounds and a calorific value of 13–15 MJ/kg, making it a potential alternative energy source. However, estimating biomass energy potential is challenged by uncertainties in production variability, residue ratios, calorific values, and conversion efficiency. To address this issue, this study aims to estimate the potential energy production from rice husk biomass as a contribution to Indonesia’s renewable energy transition within the 2025–2045 National Long-Term Development Plan (RPJPN). A stochastic Monte-Carlo simulation was applied using secondary data on national rice production, residue-to-product ratio, calorific value, and conversion efficiency. A total of 100,000 random iterations were conducted to obtain probabilistic estimates of energy potential. The results indicate that rice husk biomass can generate an average of 103.64 TWh, with a critical point of 40.04 TWh and an optimum value of 213.21 TWh. Compared to Indonesia’s projected 2045 electricity consumption, rice husk biomass contributes 10.34%–58.3% toward the RPJPN renewable energy target. These findings demonstrate that rice husk biomass holds significant potential to support national energy resilience and the transition toward a sustainable energy mix.